Bivocational and Beyond Educating for Thriving Multivocational Ministry - Stephens, Darryl (Atla Open Press, 2022)
Bivocational and Beyond provides a wide range of perspectives on faith, leadership, and learning to equip pastors and theological educators for a future in which multivocational ministry may become the norm. Bivocational ministry-also called multivocational, covocational, dual career, partially funded, non-stipendiary, or tentmaking ministry-is a topic of increasing relevance to congregational vitality and the future of the church in North America. The rise of the "gig economy," a blurring of traditional notions of sacred and secular, and missional innovation at the end of modern Christendom present challenges to received models of church and theological education. Bivocational pastors are being challenged to integrate diverse expressions of their calling, balance personal and professional obligations, overcome stigma, and achieve financial stability. Bivocational congregations are being challenged to adapt to new leadership styles and expectations of clergy and laity alike. Theological educators, including theological librarians, are also being challenged to adapt. Degree programs designed for full-time students preparing for fully funded pastoral ministry must be reassessed in light of multivocational realities. This book addresses these challenges as an opportunity for theological education and the church. Theological librarians and educators can guide congregational leaders to imagine the church in ways that transcend the "standard" model of a fully funded, professionally trained pastor of a single congregation.